When Goods Become Gods: Fractured Identities and the Call for Safe Spaces in Sports - Cynthia A White; Elizabeth Bounds (Movement and Being: The Journal of the Christian Society for Kinesiology, Leisure and Sports Studies, 2022)
What is the relationship between identity, idolatry, wholeness, and community? What are the ways in which sports culture bolsters or misdirects God-given identity? How can leaders in sports cultivate authentic, loving community that provides athletes safe spaces to explore and discern messages from the world and truth from God? In this paper, we will explore existential questions such as these. First, we will describe how identity is inherently physiological, psychological, social, and spiritual, developing subconsciously through explicit and implicit messaging. Then, we will explore the ways in which sports – organized play, human creation, and a good gift from God – can become an idol, and how idolatry both stems from and perpetuates fragmented identity. Next, we will explain what a life of wholeness means for sportspeople. Lastly, we will conclude with recommendations for leaders in sports to provide authentic and safe communities driven by love and faithfulness.
Keywords: identity; idolatry; safe places; wholeness